Fluorescent Radiosensitizing Gold Nanoparticles - Jiménez Sánchez, Gloria; Maury, Pauline; Stefancikova, Lenka; Campion, Océane; Laurent, Gautier; Chateau, Alicia; Bouraleh Hoch, Farhan; Boschetti, Frédéric; Denat, Franck; Pinel, Sophie; Devy, Jérôme; Porcel, Erika; et al. (International journal of molecular sciences, 2019)
Ultrasmall polyaminocarboxylate-coated gold nanoparticles (NPs), Au@DTDTPA and Au@TADOTAGA, that have been recently developed exhibit a promising potential for image-guided radiotherapy. In order to render the radiosensitizing effect of these gold nanoparticles even more efficient, the study of their localization in cells is required to better understand the relation between the radiosensitizing properties of the agents and their localization in cells and in tumors. To achieve this goal, post-functionalization of Au@DTDTPA nanoparticles by near-infrared (NIF) organic dyes (aminated derivative of cyanine 5, Cy5-NH2) was performed. The immobilization of organic Cy5-NH2 dyes onto the gold nanoparticles confers to these radiosensitizers fluorescence properties which can be exploited for monitoring their internalization in cancerous cells, for determining their localization in cells by fluorescence microscopy (a common and powerful imaging tool in biology), and for following up on their accumulation in tumors after intravenous injection.